Effects of flaxseed mucilage and water-to-cement ratio on the characteristics of an OPC mortar - Haris Brevet; Emmanuel Petit-Laignel; Adeline Goullieux (Academia Materials Science)
Biobased mortars are gaining interest because of the opportunity to upgrade agricultural byproducts and to reduce the environmental impact of cementitious materials. However, to overcome the drawbacks linked to the use of flax byproducts, such as mucilage and its hygroscopy, it’s necessary to study the impact of the water-to-cement ratio and the addition of mucilage on mortars. The W/C ratios range from 0.5 to 0.8 and the mucilage is added anhydrous with cement or pre-dissolved in the water. High W/C ratios affect both fresh and hardened properties of mortars. A high ratio accelerates the setting process and generates more heat released on unmodified mortars while decreasing the induction period. Conversely, when mucilage is added, the setting time is increased due to a poisoning effect affecting the hydrate growth by a chemisorption mechanism on Ca2+. This delay is higher as the W/C ratio increases and the mucilage is in-solution. Anhydrous mucilage accelerates the setting until the highest water content is reached. The undissolved polysaccharides of the mucilage cannot impact the hydration process at a W/C ratio below 0.8. Increasing the water content is beneficial for the mortar strength but an excessive W/C ratio is harmful for the unmodified mortar. Mucilage polysaccharides generate a lack of strength compared to the standard. This reduction in strengths is lowered in flexural tests due to an elastic behavior conferred by the mucilage. The changes in properties are not correlated to any mineralogical modification as shown by FTIR and TGA analyses.